2014
DOI: 10.3233/bme-141223
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs: potential biomarkers for disease diagnosis

Abstract: MicroRNAs (miRNAs) are a group of endogenous noncoding small RNAs characterized by high conservation; furthermore, various studies have shown the capability of miRNAs to impact diseases. For example, a study shows that cellfree miRNAs are stable in bodily fluids, which gives circulating miRNAs the ability to be potential biomarkers for noninvasive diagnosis. Additionally, accumulating studies have supported that miRNAs can function as suppressor genes, again demonstrating their effect on disease. This review i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 62 publications
0
12
0
1
Order By: Relevance
“…Free exRNA represents a substantial proportion of RNA in the circulation [ 33 38 ]. It is receiving much attention as potential biomarker of various diseases [ 39 , 40 ]. However, there are no prior reports nor has it been mentioned in reviews [ 41 43 ] that free exRNA can transfer functional information to acceptor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Free exRNA represents a substantial proportion of RNA in the circulation [ 33 38 ]. It is receiving much attention as potential biomarker of various diseases [ 39 , 40 ]. However, there are no prior reports nor has it been mentioned in reviews [ 41 43 ] that free exRNA can transfer functional information to acceptor cells.…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs are a class of small regulatory RNA molecules, 21-23 nucleotides in length, that negatively regulate the expression of their target genes by binding to the 3′-untranslated regions (UTR) of the corresponding mRNAs [ 3 ]. Previous studies have reported that miRNAs can act as oncogenes or tumor suppressors during the development and metastasis of osteosarcoma [ 4 , 5 ]. MiR-93 reportedly promotes the metastasis of osteosarcoma by targeting E2F1 [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last few years, miRNA studies have increased and pointed out these molecules as excellent biomarkers for different pathologies [21]. Importantly, miRNAs have especially been found altered in different cancers [22,23].…”
Section: Discussionmentioning
confidence: 99%